Astigmatism prediction in small-incision lenticule extraction. Issue 4 (April 2020) - Gyldenkerne, Anders; Hjortdal, Jesper; Ivarsen, Anders
Abstract : The magnitude of induced subjective astigmatism after SMILE for patients with preoperative exclusive spherical subjective correction was significantly related to the magnitude of the preoperative objective astigmatism. Abstract : Purpose: To investigate whether postoperative-induced refractive astigmatism after small-incision lenticule extraction (SMILE) could be predicted by preoperative objective astigmatism measured with autorefraction, keratometry, and Scheimpflug tomography. Setting: University eye clinic. Design: Retrospective case series. Methods: Only eyes without preoperative subjective astigmatism treated with SMILE for myopia were included. Postoperative subjective astigmatism was compared with preoperative objective astigmatism. Examinations were performed before SMILE and 3 months postoperatively and included subjective refraction, keratometry, autorefraction, and Scheimpflug tomographer measurements. Astigmatism was analyzed using double-angle plots and multivariate statistics. Results: A total of 358 eyes of 358 patients were included. The mean preoperative sphere was −7.33 diopter (D) ± 1.46 (SD). The postoperative spherical equivalent was −0.30 ± 0.49 D. Postoperatively, 79.6% and 98.9% of patients had a subjective cylinder ≤0.50 D and ≤1.00 D, respectively. Preoperative objective astigmatism measured with keratometry, autorefraction, and Scheimpflug tomography was significantly different ( P < .05) from postoperative subjective refraction when all patients were analyzed; for patients with postoperative refractive astigmatism ≥0.50 D, preoperative astigmatism with keratometry and Scheimpflug tomography was not significantly different from postoperative refractive astigmatism. Preoperative objective astigmatism ≥0.50 D increased the risk ratio of postoperative subjective astigmatism ≥0.50 D by 2.2 ( P < .001). Conclusions: Preoperative objective astigmatism could not be directly interchanged with postoperative subjective astigmatism, but the presence of preoperative astigmatism ≥0.50 D doubled the risk of inducing a postoperative subjective astigmatism ≥0.50 D. Extra care when performing subjective refraction should be taken in the presence of high objective astigmatism.